2013
DOI: 10.1007/s11910-013-0347-2
|View full text |Cite
|
Sign up to set email alerts
|

Response Assessment Criteria for Glioblastoma: Practical Adaptation and Implementation in Clinical Trials of Antiangiogenic Therapy

Abstract: Since 1990, the primary criteria used for assessing response to therapy in high-grade gliomas were those developed by Macdonald and colleagues, which incorporated 2-dimensional area measurements of contrast-enhancing tumor regions, corticosteroid dosing, and clinical assessment to arrive at a designation of response, stable disease, or progression. Recent advances in imaging technology and targeted therapeutics, however, have exposed limitations of the Macdonald criteria and have highlighted the need for reeva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
86
0
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(90 citation statements)
references
References 49 publications
1
86
0
3
Order By: Relevance
“…Specifically, assessment of nonenhancing tumor components was included, and a specific algorithm was used to assess pseudoprogression. 25 These adaptations are consistent with current international consensus guidelines. 26 Assessments were carried out at baseline; 28 days after completion of the concurrent-therapy phase; during cycles 2, 4, and 6 of the maintenance phase; every 9 weeks throughout the monotherapy phase; and at the time of disease progression.…”
Section: Assessmentssupporting
confidence: 79%
See 2 more Smart Citations
“…Specifically, assessment of nonenhancing tumor components was included, and a specific algorithm was used to assess pseudoprogression. 25 These adaptations are consistent with current international consensus guidelines. 26 Assessments were carried out at baseline; 28 days after completion of the concurrent-therapy phase; during cycles 2, 4, and 6 of the maintenance phase; every 9 weeks throughout the monotherapy phase; and at the time of disease progression.…”
Section: Assessmentssupporting
confidence: 79%
“…33 The adapted Macdonald Response Criteria, which were used to assess progression, anticipated some of the key features of the Response Assessment in Neuro-Oncology (RANO) Working Group criteria, which were not available at the time of the initiation of our study. 25,26 The adapted Macdonald Response Criteria addressed the observed limitations of imaging assessment by including qualitative evaluation of both noncontrast-enhancing components (by means of T 2 -weighted imaging or fluid-attenuated inversion recovery [FLAIR]) and small contrastenhancing lesions (at least one diameter <10 mm). These criteria also addressed the transient increases in tumor enhancement (pseudoprogression) associated with front-line chemoradiotherapy by standardizing the assessment of pseudoprogression with the use of a strict algorithm, resulting in lower incidences of pseudoprogression than those in previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, radiographic improvement is felt to provide a straightforward indication of anti-tumor effect because immunotherapies do not decrease tumor vessel permeability leading to pseudoresponse as been observed following anti-angiogenic agents [26]. On the other hand, worsened radiographic findings following administration of an immunotherapeutic may be more challenging to interpret.…”
Section: Complexity Of Radiographic Worsening Following Immunotherapymentioning
confidence: 99%
“…Moreover, the diagnosis and treatment of glioma are difficult, its pathology and pattern of invasion and migration are poorly understood (6,7). Several studies have reported that the pathological response of glioma, which is the malignant process of infiltration into the extensive normal tissue, is due to the activation of mitogen-activated protein kinase (MAPK), protein kinase Cα (PKCα) and matrix metalloproteinases (MMPs) (8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%